RegDemo: Preparation and Merger of Actor Data – Technical Documentation of Routines and Datasets - Wilfried Ehrenfeld (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
Primary objective of the presented routines is the mapping of cooperative relations of companies, universities, non-university research facilities and other institutions on three levels of innovation activity (joint projects; publications, patents). This includes a) the standardization and merging of the three innovation-related databases (funding catalog (“Förderkatalog”); Web of Knowledge; DPMA patents) and b) linking this combined data pool with the data from the institution data sets Amadeus and Research Explorer by means of record linkage procedures. For this project the merger comprises the six regions considered in the RegDemo project. Spatial planning regions (“Raumordnungsregionen”) are used for delimitation: 501 - Aachen; 513 - Siegen; 602 - Nordhessen (= “Kassel”); 1302 – Mittleres Mecklenburg/Rostock (= “Rostock”); 1401 - Oberes Elbtal/Osterzgebirge (= “Dresden”); 1504 - Magdeburg. – – Übergeordnetes Ziel der hier vorgestellten Routinen ist die Abbildung von Kooperationsbeziehungen von Unternehmen, Universitäten, außeruniversitären Forschungseinrichtung sowie sonstiger Institutionen auf drei Ebenen von Innovationstätigkeit (Verbundprojekte; Publikationen; Patente). Dazu werden a) die drei innovationsbezogenen Datenbanken (Förderkatalog; Web of Knowledge; DPMA Patente) vereinheitlicht und zusammengeführt sowie b) diese kombinierten Datenbestände mittels Record-Linkage-Techniken mit den Daten aus den Institutionendatensätzen Amadeus und Research Explorer verknüpft. Die Zusammenführung erstreckt sich für dieses Projekt auf die sechs Fallregionen, die in RegDemo vorgesehen sind. Die Abgrenzung erfolgt anhand von Raumordnungsregionen: 501 - Aachen; 513 - Siegen; 602 - Nordhessen (= ,,Kassel“); 1302 – Mittleres Mecklenburg/Rostock (= ,,Rostock“); 1401 - Oberes Elbtal/Osterzgebirge (= ,,Dresden“); 1504 - Magdeburg.
Keywords: 330